REFORMULATING CARBON TAX IN INDONESIA: ADVANCING THE GREEN TAX REFORM IN CLIMATE CHANGE MITIGATION - Arifia, Septika Nanda; Novikasari, Siti Rahma; Perdana, Muhammad Anugerah; Maharani, Galuh Putri (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Climate change mitigation has emerged as a pivotal global concern warranting considerable attention. In response to the escalating climate crisis, the